How COVID-19 affected corporate dividend decisions: Novel evidence from emerging countries - Abdullah AlGhazali; Ilker Yilmaz (Financial Internet Quarterly, 2023)
The study aims to investigate the corporate dividend policy decisions in emerging countries during the COVID-19 pandemic. Our sample consists of 5,869 publicly listed firms from 29 emerging countries to explicate the observed trends in dividend policy during the pandemic. Logistic regressions are used to investigate the main factors that drive the propensity to change dividend payouts. Our analysis reveals that most firms opted to either increase or decrease their dividends, with a minority proportion deciding to maintain dividends. Notably, our findings demonstrate that firm profitability is the main driver of all types of dividend changes, except when firms opt to maintain or decrease dividends. Moreover, we find that when firms reduce dividends by over 70%, profitability emerges as a crucial determinant, thus bolstering the signaling hypothesis. The results are robust to sample size sensitivity and different levels of dividend changes. The findings of the study might have practical implications for corporate managers and policymakers in designing dividend decisions and policies under uncertain conditions. This research underscores the impact of the COVID-19 pandemic on corporate dividend policy in emerging countries and emphasizes the need to consider the level of dividend changes in exploring the dividend puzzle.
Keywords: G30; G32; G35; 330; Dividend policy; COVID-19; Pandemic; Profitability; Emerging countries